IMPACTS OF ATTABAD LAKE (PAKISTAN) AND ITS FUTURE OUTLOOK - Iqbal, Muhammad Jawed; Shah, Fiaz Hussain; Chaudhry, Anwar Ul Haq; Baig, Muhammad Naseem (European Scientific Journal, ESJ, 2014)
Due to geological, hydrological and anthropogenic variations in Northern Areas of Pakistan, the possibility of hazards like earthquake, flash floods, landslide and Glacial Lake Outburst Flood (GLOF) have increased manifolds. The incident of Attabad landslide on 4th January 2010 blocking the Hunza River and resulting in the formation of huge lake as a sequel to Astore earthquake in 2002 and Kashmir earthquake in 2005 is a testimony to the fact hazards turn into disasters causing loss and damage to lives, properties, assets and environment. There are multiple reasons ranging from global warming, deforestation, unplanned settlements, population growth, aggressive farming and host of other man induced activities which have made the Northern Areas of Pakistan hazards prone and are likely to pose continuous threat if requisite preparation and response options are not considered well in advance. In case of Attabad landslide, viewing from the prism of disaster risk management the response of Gilgit-Baltistan and Federal Governments has though not been up to the mark yet mobilization of resources and opinion to manage the disaster leaves a promising environment of hope and capacity which can be further developed to more resilient respondent provided little extra deliberations are done and attention is paid. The solution to Attabad landslide dam crisis lies in reducing the risk by either draining out the lake completely or making a reliable structure with proper design for flow of the water from the lake.